Proteomic techniques for characterisation of mesenchymal stem cell secretome - Kupcova Skalnikova, Helena (Biochimie, 2013)
Mesenchymal stem cells (MSCs) are multipotent cells with a substantial potential in human regenerative medicine due to their ability to migrate to sites of injury, capability to suppress immune response and accessibility in large amount from patient's own bone marrow or fat tissue. It has been increasingly observed that the transplanted MSCs did not necessarily engraft and differentiate at the site of injury but might exert their therapeutic effects through secreted trophic signals. The MSCs secrete a variety of autocrine/paracrine factors, called secretome, that support regenerative processes in the damaged tissue, induce angiogenesis, protect cells from apoptotic cell death and modulate immune system. The cell culture medium conditioned by MSCs or osteogenic, chondrogenic as well as adipogenic precursors derived from MSCs has become a subject of intensive proteomic profiling in the search for and identification of released factors and microvesicles that might be applicable in regenerative medicine. Jointly with the methods for MSC isolation, expansion and differentiation, proteomic analysis of MSC secretome was enabled recently mainly due to the extensive development in protein separation techniques, mass spectrometry, immunological methods and bioinformatics. This review describes proteomic techniques currently applied or prospectively applicable in MSC secretomics, with a particular focus on preparation of the secretome sample, protein/peptide separation, mass spectrometry and protein quantification techniques, analysis of posttranslational modifications, immunological techniques, isolation and characterisation of secreted vesicles and exosomes, analysis of cytokine-encoding mRNAs and bioinformatics.
Keywords: Secretome; Exosomes; ASCs; MS; výpočetní biologie; buňky kostní dřeně; tuková tkáň; 2D gelová elektroforéza; Culture Media, Conditioned; 2-DE; 2-dimensional gel electrophoresis; buněčná diferenciace; conditioned medium; selected reaction monitoring; TNF; buněčné kultury; Electrophoresis, Gel, Two-Dimensional; mass spectrometry; tumour necrosis factor; exozómy; Mass Spectrometry; endoplasmic reticulum; TEM; MSCs; kultivační média speciální; proteomika; Conditioned medium; mesenchymal stem cells; SRM; Animals; Exosome; lidé; Adipose Tissue; Humans; zvířata; Cell Culture Techniques; transmission electron microscopy; ER; cell surface capturing; CSC; hmotnostní spektrometrie; Proteomics; CM; adipose stem/stromal cells; Bone Marrow Cells; Mesenchymal Stem Cells; Mesenchymal stem cells; Computational Biology; Cell Differentiation; mezenchymální kmenové buňky